Poem of Parmenides - Mrówka, Kazimierz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
This is a new translation of the Fragments of Parmenides of Elea, the fifth century B.C. thinker. The text includes: a Greek poem with the fragments B 9-17, B 19, a critical apparatus which takes into consideration some new editions and a new English translation.